The impact of neonatal posthemorrhagic hydrocephalus of prematurity on family function at preschool age. (October 2019) - Agajany, Netanel; Gigi, Moran; Ross, Jessica; Roth, Jonathan; Eshel, Rina; Constantini, Shlomi; Bassan, Haim
Abstract: Aims: To determine the impact on families (IOF) of former preterm infants (gestational age < 32 weeks) after posthemorrhagic hydrocephalus requiring shunt (PHH-S), and to identify risk factors of family dysfunction. Study design: 38 preterm infants with PHH-S were matched for gestational age, birthweight, and gender with preterm infants with normal cranial ultrasonography. IOF questionnaire was administered at 5.7 ± 2 years (higher IOF score indicates worse impact). Results: Families of PHH-S children exhibited significantly worse IOF compared to controls in financial (9.2 ± 2.2 vs 5.9 ± 1.4), family-personal (26.6 ± 5.2 vs 20.2 ± 2.8), and disruptive social (21.4 ± 4.9 vs 16.7 ± 3.1) domains ( P < 0.001). Multivariate regression incorporating neonatal risk factors revealed an independent effect of parenchymal brain involvement (β:0.4, P:0.002 ) and neonatal seizures (β:0.3, p:0.007 ) on total IOF. Neurosensory morbidity was significantly higher in the PHH-S group, including cerebral palsy (81.6%), epilepsy (47.4%), problems with vision (63.2%), feeding (39.5%) and hearing (18.4%), chronic health problems (44.7%) and hospital admissions in the last 6 months (44.7%). Worse IOF scores of PHH-S families were associated with socioeconomic status and neurodevelopmental morbidities: cerebral palsy severity, feeding problems, number of neurosurgeries, low cognitive, personal-social, and adaptive scores ( P < 0.05). Multivariate analysis indicated an independent contribution from cerebral palsy severity (β:0.5, p:0.002 ) and socioeconomic status (β:-0.4, P: 0.01). Conclusions: Families of preterm children after PHH-S exhibit significantly worse IOF scores compared to families of preterm peers. Worse IOF is associated with severe hemorrhage, neurodevelopmental morbidities and socioeconomic status. A family centered intervention is warranted after PHH-S. Highlights: Posthemorrhagic hydrocephalus of prematurity has a negative impact on family function at preschool age. Worse impact on family is associated with severe cerebral injury, cerebral palsy severity and socioeconomic scores. A family centered intervention is warranted after posthemorrhagic hydrocephalus of prematurity.